Madani Center Rokan Hulu Mosque: Management of Da'wah Media and Its Impact on the Quality of Community Religion - Rusdi, Muhamad; Rubino, Rubino (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This article discusses the Madani Islamic Center Rokan Hulu mosque in developing da'wah media and influence on society in religious life. Along with the development of the Times that already refers to the contribution of technology, the Madani Islamic Center Mosque also uses technology in preaching dynamically and to see if the media used has a serious impact on the religious quality of the community in Rokan Hulu. This study uses qualitative descriptive method with the type of Field Research (field research). The source of data in this study is information directly from the informant by using a semi-structured interview system. In data analysis techniques, researchers collect data that is further reduced, presented and then concluded. The results of this study indicate the success of the media da'wah Masjid Madani Islamic Center Rokan Hulu either from planning, organizing, implementation and supervision has brought positive changes for the people of Rokan Hulu. By using da'wah media in the form of radio and television is proven to improve the quality of religious understanding of the people of Rokan Hulu, so as to make people always do good and leave evil in accordance with the conveyed Al-Qur'an and Hadith. Artikel ini membahas tentang Masjid Madani Islamic Center Rokan Hulu dalam mengembangkan media dakwah serta pengaruh terhadap masyarakat dalam kehidupan keagamaan. Seiring perkembangan zaman yang sudah mengacu kepada kontribusi teknologi maka Masjid Madani Islamic Center ikut menggunakan teknologi dalam berdakwah secara dinamis dan melihat apakah media yang digunakan berdampak serius kepada kualitas keagamaan masyarakat di Rokan Hulu. Penelitian ini menggunakan metode deskriptif kualitatif dengan jenis penelitian lapangan (field research). Sumber data dalam penelitian ini adalah informasi langsung dari informan dengan menggunakan sistem wawancara semi terstruktur. Pada teknik analisis data, peneliti mengumpulkan data yang selanjutnya direduksi, disajikan kemudian disimpulkan. Hasil penelitian ini menunjukkan keberhasilan media dakwah Masjid Madani Islamic Center kabupaten Rokan Hulu baik itu dari perencanaan, pengorganisasian, pelaksanaan dan pengawasan telah membawa perubahan positif bagi masyarakat Rokan Hulu. Dengan menggunakan media dakwah berupa radio dan televisi terbukti dapat meningkatkan kualitas pemahaman agama masyarakat Rokan Hulu, sehingga membuat masyarakat senantiasa mengerjakan kebaikan dan meninggalkan keburukan sesuai dengan yang disampaikan Al-Qur’an dan Hadist.